IT savvy : what top executives must know to go from pain to gain - Weill, Peter; Ross, Jeanne W. (Boston, Mass. : Harvard Business Press, 2009)
Tired of spending money on IT without understanding your investment? Not getting the results you need in the time frame you expected? Here, the authors identify five imperatives that will help you drive value from IT, with detailed explanations on their implementation.
Transforming IT from strategic liability to strategic asset -- Defining your operating model -- Revamping your IT funding model -- Building a digitized platform -- Allocating decisions rights and accountability -- Driving value from IT -- Leading an IT-savvy firm.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Information technology -- Management; Information technology -- Management; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; elektronické knihy; electronic books